Ferric iron reductases and their contribution to unicellular ferrous iron uptake - Cain, Timothy J. (J Inorg Biochem, 2021)
Iron is a necessary element for nearly all forms of life, and the ability to acquire this trace nutrient has been identified as a key virulence factor for the establishment of infection by unicellular pathogens. In the presence of O(2), iron typically exists in the ferric (Fe(3+)) oxidation state, which is highly unstable in aqueous conditions, necessitating its sequestration into cofactors and/or host proteins to remain soluble. To counter this insolubility, and to compete with host sequestration mechanisms, many unicellular pathogens will secrete low molecular weight, high-affinity Fe(3+) chelators known as siderophores. Once acquired, unicellular pathogens must liberate the siderophore-bound Fe(3+) in order to assimilate this nutrient into metabolic pathways. While these organisms may hydrolyze the siderophore backbone to release the chelated Fe(3+), this approach is energetically costly. Instead, iron may be liberated from the Fe(3+) - siderophore complex through reduction to Fe(2+), which produces a lower-affinity form of iron that is highly soluble. This reduction is performed by a class of enzymes known as ferric reductases. Ferric reductases are broadly-distributed electron-transport proteins that are expressed by numerous infectious organisms and are connected to the virulence of unicellular pathogens. Despite this importance, ferric reductases remain poorly understood. This review provides an overview of our current understanding of unicellular ferric reductases (both soluble and membrane-bound), with an emphasis on the important but underappreciated connection between ferric-reductase mediated Fe(3+) reduction and the transport of Fe(2+) via ferrous iron transporters.